Offline Payment of Central Bank Digital Currency Based on a Trusted Platform Module - Jaeho Yoon; Yongmin Kim (Journal of Cybersecurity and Privacy)
The implementation of Central Bank Digital Currencies (CBDCs) faces significant challenges in achieving the same level of anonymity and convenience in offline transactions as cash. This limitation imposes considerable constraints on the development and widespread adoption of CBDCs. Unlike cash, digital currencies, similar to other electronic payment methods, necessitate internet or other network connectivity to verify payment eligibility. This study proposes a secure offline payment model for CBDCs that operates independently of internet or network connections by utilizing a Trusted Platform Module (TPM) to enhance the security of digital currency transactions. Additionally, the monotonic counter, the basic component of the TPM, is integrated into this model to prevent double spending in a completely offline environment. Our research presents a protocol model that combines these easily implementable technologies to facilitate the efficient processing of transactions in CBDCs entirely offline. However, it is crucial to acknowledge the security implications associated with the TPMs and near-field communications upon which this protocol relies.